(untitled) (LEARNing Landscapes, 2012)
In this interview, developmental psychologist, professor, and author Howard Gardner describes his early interest in creativity and explains why he wanted to study creativity from a different perspective than what had been done in the past. He shares why studying creativity through the biographies of creative people provides more insight than using creativity tests that may be as limited as IQ tests. The creative leaders he studied in his book Creating Minds proved to have an unusual blend of intelligences—not just those intelligences obviously related to their field. He explains that creativity is about one’s personality, the willingness to take risks, and being a certain kind of person rather than having a particular set of cognitive skills. Finally, he comments on creativity in today’s society.